Examination of Effect of Electrochemically Activated Water Solutions on Candida albicans After Different Periods of Storage (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
Studies to determine the sensitivity of Candida albicans to anolyte and catholyte of 0.5% NaCl and a combination of 0.5% NaCl and 0.5% Na2CO3 were performed. Both anolytes killed the tested strains in suspensions (106 cells/ml) within 5 min. The catholytes showed low antimicrobial activity. The inhibitory properties of the tested anolytes were fully preserved over a period of 2 months when stored in the dark at room temperature, but of the catholytes - for no more than 2 weeks. These results show that anolytes are promising antimicrobial agents with very high activity against C. albicans.